2016
DOI: 10.1016/j.jenvp.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Does perceived restorativeness mediate the effects of perceived biodiversity and perceived naturalness on emotional well-being following group walks in nature?

Abstract: Does perceived restorativeness mediate the effects of perceived biodiversity and perceived naturalness on emotional wellbeing following group walks in nature?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
128
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 127 publications
(163 citation statements)
references
References 90 publications
11
128
0
2
Order By: Relevance
“…This is congruence with earlier studies that showed mediation effect of perceived restorativeness on the effect of environmental qualities on emotional well-being (Carrus et al 2015;Marselle et al 2016) and university students better quality of life Hipp et al (2016). The association of PSD and restorativeness has been demonstrated by previous studies (Peschardt and Stigsdotter 2013;Stigsdotter et al 2017;Stoltz et al 2016).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This is congruence with earlier studies that showed mediation effect of perceived restorativeness on the effect of environmental qualities on emotional well-being (Carrus et al 2015;Marselle et al 2016) and university students better quality of life Hipp et al (2016). The association of PSD and restorativeness has been demonstrated by previous studies (Peschardt and Stigsdotter 2013;Stigsdotter et al 2017;Stoltz et al 2016).…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, this is the first study in which the mediator effect of perceived restorativeness on the relationship between PSD and restoration experience is examined. Similar with other studies that showed mediation effect of perceived restorativeness (Carrus et al 2015;Hipp et al 2016;Marselle et al 2016), this study showed that perceived restorativeness is important in shaping relationship between PSD and restoration experience. Greater restoration experience highly depends on effect of PSDs on perceived restorativeness, and then experience of restorative outcomes.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations